Monitoring vegetation cover trends in the steppe region of western Algeria using MODIS imagery - Kious, Chahrazed; Maatoug, M’hamed; Bouacha, Mohamed Islam; Maatoug, Zakaria Zineddine (Universitas Sebelas Maret, 2024)
The steppe region of Chehaima (Tiaret Province, northwestern Algeria) covers an area of 2,202 km², representing 10.94% of the total area of Tiaret. This study identified the ecological state of the area using a spatial theme from a 24-year synchronized moderate-resolution imaging spectroradiometer (MODIS) satellite image campaign (2000–2023). The adopted method consists of analyzing spectral indices (normalized difference vegetative index, low surface temperature (LST), and soil moisture index) from MODIS sensors (MOD13Q1), making it possible to evaluate the spatiotemporal dynamics of the vegetation in the study area and to identify regions degraded by several biotic and abiotic factors. The results show a vegetation cover rate of intense fluctuations in unfavorable conditions over 24 years. The percentage of plant growth recorded does not exceed 32%. The abundance of LST vegetation decreases when the LST exceeds 35°C, with a soil that has a water deficit. The De Martonne aridity index (I) classifies the study area as a lower semiarid bioclimatic zone. These indicators made it possible to determine the spatiotemporal dynamics of vegetation, which modifies the plant cover, leading to the loss of native species such as alfa Stipa tenacissima L. Defensive measures are necessary over large areas of the study area to allow successful protection of steppe rangelands through a sustainable conservation strategy, preserving endemic species, stabilizing dunes, and adopting the steppe rotation system.